Awareness of Hypertension, Hypercholesterolemia, and Diabetes Mellitus and Associated Characteristics in Russian Adults - Filip Sahatqija; Monica Hunsberger; Sarah Cook; Kamila Kholmatova; Marina Shapkina; Sofia Malyutina; Alexander V. Kudryavtsev (International Journal of Hypertension)
Russia has higher cardiovascular disease (CVD) mortality compared to other European countries. The major CVD risk factors are age, male sex, and three conditions, namely hypertension, hypercholesterolemia, and diabetes mellitus (DM). This study aimed to assess awareness of these three conditions among Russian adults (N = 3803) and the associated socio-demographic, lifestyle, and health characteristics. We used cross-sectional data from a randomly drawn population-based sample of Russians aged 35–69 years, who participated in the Know Your Heart (KYH) study conducted in Arkhangelsk and Novosibirsk between 2015–2018. Participants’ self-reported awareness of hypertension, hypercholesterolemia, and DM was assessed against the measures at the KYH health check (blood pressure, cholesterol, HbA1c and/or use of medication for each condition). Prevalence estimates for the awareness were age- and sex-standardized to the Standard European Population. Socio-demographic, lifestyle, and health-related correlates of the awareness were investigated using logistic regression modelling. Among participants with hypertension (N = 2206), hypercholesterolemia (N = 3171), and DM (N = 329) recorded at a health check, 79%, 45%, and 61% self-reported these conditions, respectively. Higher awareness of hypercholesterolemia and hypertension was associated with older age, female sex, nonsmoking status, obesity, and history of CVD diagnoses. Low household income and history of CVD diagnoses were associated with being aware of DM. The awareness rates of hypertension were relatively high, whereas awareness rates of hypercholesterolemia and DM were relatively low. CVD prevention and early intervention could be improved in Russia through increasing the awareness of the risk factors.